1985
DOI: 10.1080/00015128509435768
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Selenium Supplementation of Animal Feeds in Norway

Abstract: The effect of selenium supplementation of animal feeds in Nonray. Received Sept. 26, 1984. Acta Agric. Scand. 35: [139][140][141][142][143][144] 1985. Selenium supplementation of feeds HDS introduced in Nonmy in 1980. The effect of this supplementation on selenium status of animals has been investigated. In general, the supplementation resulted in increased selenium levels in animals as well as in animal products. The supply of selenium seems to be quite satisfactory as regards poultry and slaughter pigs whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
(4 reference statements)
3
9
0
Order By: Relevance
“…The mean Se concentrations in cow's milk during winter and spring were signi"cantly higher than those during summer and autumn. This agrees with Fr+slie et al (1985), Koops et al (1989) and Olson and Palmer (1984), who found Se concentrations in milk during winter to be higher than those during summer (Table 4). The contents of Fe and Cu remained approximately constant during the year.…”
Section: Resultssupporting
confidence: 93%
“…The mean Se concentrations in cow's milk during winter and spring were signi"cantly higher than those during summer and autumn. This agrees with Fr+slie et al (1985), Koops et al (1989) and Olson and Palmer (1984), who found Se concentrations in milk during winter to be higher than those during summer (Table 4). The contents of Fe and Cu remained approximately constant during the year.…”
Section: Resultssupporting
confidence: 93%
“…Mean selenium levels among lactating cows, dry cows and pregnant heifers differed significantly, both in blood (Material I) and in plasma (Material 11) F a b l e 2). The results presented in Tables 1, 2 and 3 support Frgslie et al (1979Frgslie et al ( , 1980Frgslie et al ( , 1985 who found that selenium supply for Norwegian cattle may be marginal, especially for animals given feed in which only a small amount of imported feed concentrates is incorporated. In The relationship between plasma and blood selenium levels is illustrated in Fig.…”
Section: Resultssupporting
confidence: 92%
“…Selenium has therefore been added to compound concentrates (0.15 mdkg until April 1985, thereafter 0.20 m a g ) , mineral mixtures (10 mgkg) and supplementary feeds since 1980. However, the selenium supply still seems to be marginal in ruminants fed mainly on roughages (Frgslie et al, 1985). Accordingly, more than 1200 cases of muscular dystrophy in cattle were reported in 1983 among a population of approximately 380000 cow equivalents (Veterinary statistics, 1983(Veterinary statistics, , 1985.…”
Section: Introductionmentioning
confidence: 99%
“…There are appreciable regional differences in Se status within the country, most clearly demonstrated in sheep (Sivertsen 2004). Vit E and Se have been added to commercial concentrates for many years (Frøslie et al 1985). In spite of this, a previous study of 64 Norwegian dairy herds showed a substantial fraction at marginal Se levels (Ropstad et al 1987).…”
Section: Introductionmentioning
confidence: 99%